Perkembangan Masa Bayi dan Implikasinya pada Pendidikan - Sartika; Larissa Putri Isyara; Linda; Amilda; Kasinyo Harto (Lembaga Anotero Scientific, 2024)
This research aims to examine development during infancy and its implications for early childhood education. Using the library study research method, this research collects and analyzes relevant literature from various academic sources such as books, scientific journals and articles. Data is classified based on main themes such as stages of infant development, factors influencing development, and implications for education. The research results show that infancy development includes physical, cognitive, emotional and social aspects that are interrelated. Factors such as genetics, environment, nutrition, and social interactions play an important role in such development. Implications for early childhood education include the need for a holistic and individualized approach in supporting children's development. Educators and parents are advised to provide a stimulative and responsive environment and implement educational strategies that are appropriate to the child's developmental stages. This research provides practical recommendations to support optimal development of babies through appropriate educational interventions from an early age.